2022
DOI: 10.3390/ijerph19042399
|View full text |Cite
|
Sign up to set email alerts
|

Workaholism and the Enactment of Bullying Behavior at Work: A Prospective Analysis

Abstract: Despite the fact that workaholism and workplace aggressive behavior share many correlates, such as neuroticism, hostility, and negative affectivity, little is known about their relationship, with most evidence on both phenomena coming from cross-sectional studies. In the present study, we contributed to a better understanding of the antecedents of enacted workplace bullying behavior (i.e., perpetration of bullying), and the potential interpersonal implications of workaholism, by investigating their cross-lagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Indeed, similar studies investigating workplace bullying from the passive perspective have found other work environment stressors, such as job demands, that positively relate to bullying victimization [ 48 ]. Furthermore, studies exploring workplace bullying from the active perspective have also found that work environment factors such as organizational justice, organizational trust, and workaholism are also related to bullying perpetration [ 49 , 50 ]. As this study has found that managerial competencies, which alter and improve the interaction of employees with their work environment, moderate employee stress from poor working environments, managerial competencies may not just decrease the frequency of employees being bullied but may also decrease the frequency of which employees bully.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, similar studies investigating workplace bullying from the passive perspective have found other work environment stressors, such as job demands, that positively relate to bullying victimization [ 48 ]. Furthermore, studies exploring workplace bullying from the active perspective have also found that work environment factors such as organizational justice, organizational trust, and workaholism are also related to bullying perpetration [ 49 , 50 ]. As this study has found that managerial competencies, which alter and improve the interaction of employees with their work environment, moderate employee stress from poor working environments, managerial competencies may not just decrease the frequency of employees being bullied but may also decrease the frequency of which employees bully.…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation is related to the existing contradictions in the conceptualization and interpretation of the focal phenomenon of our study (i.e., work addiction). Although it is generally considered as a genuine addiction [ 7 , 53 ], in the Diagnostic and Statistical Manual of Mental Disorders [ 54 ] it has not been formally defined as such yet. Probably one of the most significant reasons for this is the lack of clarity among different forms of excessive work [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such over-commitment to work has been used in literature to describe the notion of “work addiction”. According to the authors [ 7 ], the underlying aspect of this phenomenon is a persistent psychological dysfunction. It is, therefore, not surprising that researchers think of work addiction as a negative entity.…”
Section: Introductionmentioning
confidence: 99%
“…Findings have supported a negative view of work addiction, documenting its relationships with poor well-being (Shimazu et al, 2015), anxiety, depression (Serrano-Fern andez et al, 2021), burnout (Sun et al, 2022), elevated blood pressure (Balducci et al, 2021), sleep problems and the risk of cardiovascular disease (Salanova et al, 2016). Additionally, the notion that work addicts may perform better than their colleagues has been strongly questioned, since the former are characterized by aspects not helpful in performing the job (Balducci et al, 2022). All this implies little advantage of being addicted not only to individuals themselves but also to organizations.…”
Section: Introductionmentioning
confidence: 98%
“…, 2016). Additionally, the notion that work addicts may perform better than their colleagues has been strongly questioned, since the former are characterized by aspects not helpful in performing the job (Balducci et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%